2013
DOI: 10.1186/1465-9921-14-11
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose CT measurements of airway dimensions and emphysema associated with airflow limitation in heavy smokers: a cross sectional study

Abstract: BackgroundIncreased airway wall thickness (AWT) and parenchymal lung destruction both contribute to airflow limitation. Advances in computed tomography (CT) post-processing imaging allow to quantify these features. The aim of this Dutch population study is to assess the relationships between AWT, lung function, emphysema and respiratory symptoms.MethodsAWT and emphysema were assessed by low-dose CT in 500 male heavy smokers, randomly selected from a lung cancer screening population. AWT was measured in each lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 34 publications
(55 reference statements)
1
28
0
Order By: Relevance
“…The finding that CT-quantified emphysema is associated with accelerated lung function decline seems robust given the fact that several other groups have reported similar findings [5][6][7][8][9]. YUAN et al [7] showed that there was a trend between automatically quantified low-attenuation areas on CT and follow-up lung function in smokers without COPD.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…The finding that CT-quantified emphysema is associated with accelerated lung function decline seems robust given the fact that several other groups have reported similar findings [5][6][7][8][9]. YUAN et al [7] showed that there was a trend between automatically quantified low-attenuation areas on CT and follow-up lung function in smokers without COPD.…”
Section: Discussionmentioning
confidence: 64%
“…However, they only reported results from univariate analyses and did not provide effect sizes. Other cross-sectional studies have shown that a higher airway wall thickness is associated with lower pulmonary function and the presence of COPD [5,[23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, computed tomography (CT) can be used to more accurately measure the dimensions of the airway wall. Previous studies using low-dose CT have assessed airway dimensions, such as lumen area or diameter, or Pi10 with different airway sampling methods, particularly in relation to airflow limitation, respiratory symptoms, emphysema, and smoking habits (4). Research by Nakano and colleagues (1) revealed that CT measurements of larger airways could be used to estimate the dimensions of the small conducting airways.…”
Section: P = 86 3 10mentioning
confidence: 99%
“…AWT in COPD depends on the patient population and methods used to measure AWT (5-7). We used the actually measured AWT at a fixed lumen diameter in all lobes (4).…”
Section: P = 86 3 10mentioning
confidence: 99%